2014
DOI: 10.18632/oncotarget.1886
|View full text |Cite
|
Sign up to set email alerts
|

Minoxidil may suppress androgen receptor-related functions

Abstract: Although minoxidil has been used for more than two decades to treat androgenetic alopecia (AGA), an androgen-androgen receptor (AR) pathway-dominant disease, its precise mechanism of action remains elusive. We hypothesized that minoxidil may influence the AR or its downstream signaling. These tests revealed that minoxidil suppressed AR-related functions, decreasing AR transcriptional activity in reporter assays, reducing expression of AR targets at the protein level, and suppressing AR-positive LNCaP cell grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 49 publications
2
21
0
Order By: Relevance
“…Minoxidil was first developed to act as antihypertension drug, but the people were found to have the side effect of hypertrichosis, an abnormal amount of hair growth over the body23. Previous studies reported some possible mechanisms of minoxidil to promote the hair growth: (i) minoxidil increase the hair follicle size, reduction on telogen follicles and increase the proportion of follicles in anagen24; (ii) minoxidil promotes hair growth via suppress androgen receptor-related functions25; (iii) minoxidil stimulates cell growth, delay cell senescence2026 and the stimulation of VEGF and prostaglandin synthesis27. Although, the mechanism of minoxidil action on hair growth is still unclear, it became a common medication for alopecia treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Minoxidil was first developed to act as antihypertension drug, but the people were found to have the side effect of hypertrichosis, an abnormal amount of hair growth over the body23. Previous studies reported some possible mechanisms of minoxidil to promote the hair growth: (i) minoxidil increase the hair follicle size, reduction on telogen follicles and increase the proportion of follicles in anagen24; (ii) minoxidil promotes hair growth via suppress androgen receptor-related functions25; (iii) minoxidil stimulates cell growth, delay cell senescence2026 and the stimulation of VEGF and prostaglandin synthesis27. Although, the mechanism of minoxidil action on hair growth is still unclear, it became a common medication for alopecia treatment.…”
Section: Discussionmentioning
confidence: 99%
“…We had tested the effects of 8 of these 10 candidates on AR transcriptional reporter assay and found some of these candidates could really suppress AR transcriptional activity as shown in Figure 2B . Minoxidil also presented in the top 30 candidates and had been demonstrated to suppress AR related function [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…After incubation for 16 h, cells were treated with ethanol, 10 nM DHT, or 0.01–10 μM HWC-489 or LHJ-647 for an additional 16 h. Luciferase activity in cell lysates was determined and normalized to protein concentrations. Relative luciferase activity was calculated using the luciferase reporter assay system [ 18 ]. (A) PC-3 cells were co-transfected with 350 ng pCDNA3-flag-hAR-N (residues 1–506), 350 ng pCDNA3-hAR-C (residues 556–919), and 300 ng MMTV-Luc plasmids.…”
Section: Resultsmentioning
confidence: 99%
“…Although minoxidil has been used for more than 30 years to treat AGA, its precise mechanism of action on hair growth remains elusive ( Messenger and Rundegren, 2004 ). Several primary mechanisms of minoxidil action are proposed: (a) minoxidil suppresses AR-mediated functions by decreasing AR transcriptional activity and reducing the expression of AR targets at the protein level ( Hsu et al, 2014 ), (b) minoxidil exerts anagen prolongation effects by activating β-catenin pathway in dermal papilla cells ( Kwack et al, 2011 ), (c) minoxidil stimulates hair follicle angiogenesis by inducing the expression of VEGF in dermal papilla cells ( Lachgar et al, 1998 ), (d) minoxidil shows a cytoprotective activity by activating prostaglandin synthase-1 ( Michelet et al, 1997 ), and (e) minoxidil increases blood flow by dilating hair follicle arteries ( Messenger and Rundegren, 2004 ). Finasteride is a DHT synthesis inhibitor, which suppresses the conversion of testosterone to DHT by binding to 5α-reductase ( Varothai and Bergfeld, 2014 ; Kelly et al, 2016 ; Adil and Godwin, 2017 ).…”
Section: Introductionmentioning
confidence: 99%